SEC Scrutiny and the Evolution of Non-GAAP Reporting - Kolev, Kalin; Marquardt, Carol A.; McVay, Sarah E. (The Accounting Review, 2008)
We empirically examine the effects of intensified scrutiny over non-GAAP reporting on the quality of non-GAAP earnings exclusions. We find that, on average, exclusions are of higher quality (i.e., more transitory) following intervention by the Securities and Exchange Commission (SEC) into non-GAAP reporting. We further find that firms that stopped releasing non-GAAP earnings numbers after the SEC intervention had lower quality exclusions in the pre-intervention period. These results are consistent with the SEC's objectives of improving the quality of non-GAAP earnings figures. However, when we decompose total exclusions into special items and other exclusions, we find evidence that the quality of special items has decreased in the post-intervention period, which suggests that managers adapted to the new disclosure environment by shifting more recurring expenses into special items. This suggests that there may be unintended consequences arising from the heightened scrutiny over non-GAAP reporting.